2022
DOI: 10.2147/jpr.s355096
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Treatment, and Management of Painful Scar: A Narrative Review

Abstract: Painful scars can develop after surgery or trauma, with symptoms ranging from a minor itch to intractable allodynia. The problem of the painful scar may involve both intraneural and extraneural structures, requiring a systematic approach to diagnosis and treatment of this neuropathic pain condition that can impact quality of life and function profoundly. In this review, we outline the algorithm for the diagnosis, management, medical and surgical treatment of painful scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 106 publications
0
11
0
1
Order By: Relevance
“…[12] In VAS scores, patients in the general anesthesia group had less pain on a postoperative day than those in the surface anesthesia group, and one study found that intraoperative administration of intravenous anesthetic medication for analgesia reduced the incidence of chronic postoperative pain, which is consistent with the results of this study. [15] Brendan et al found that only 25% of patients with hypertrophic scars who underwent laser treatment under general anesthesia experienced postoperative pain, and general anesthesia was the ideal choice.…”
Section: Discussionmentioning
confidence: 99%
“…[12] In VAS scores, patients in the general anesthesia group had less pain on a postoperative day than those in the surface anesthesia group, and one study found that intraoperative administration of intravenous anesthetic medication for analgesia reduced the incidence of chronic postoperative pain, which is consistent with the results of this study. [15] Brendan et al found that only 25% of patients with hypertrophic scars who underwent laser treatment under general anesthesia experienced postoperative pain, and general anesthesia was the ideal choice.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic pain and dyspareunia are two of the most difficult clinical problems to assess and treat 36 . Painful scars can occur after all types of surgery, and the scar tissue extends below the skin and crosses tissue planes, creating an opportunity for nerve injury or entrapment 37 . As suggested by Steege et al, obstetricians and gynecologists may benefit from learning from the literature of other specialties that deal with pain related to surgical scars 36 .…”
Section: Discussionmentioning
confidence: 99%
“…37 As suggested by Steege et al, obstetricians and gynecologists may benefit from learning from the literature of other specialties that deal with pain related to surgical scars 36. …”
mentioning
confidence: 99%
“…10 Chronic pain in scars of moderate-to-severe intensity occurs in 19% of adult Europeans 9 ; scars also lead to a restricted range of motion resulting in the reduction of quality of social and work life. 1 The first aid in pain reduction is analgesia, which can be applied topically or administered systemically. Unfortunately, oftentimes analgesia is not completely effective and does not avoid strong psychological repercussions: Recent estimates suggest that more than 20% of European patients with chronic pain have been concomitantly diagnosed with depression.…”
Section: Introductionmentioning
confidence: 99%
“…9 Different treatment approaches such as electrotherapy, laser, ultrasound, acupuncture, and intense pulsed light are routinely used to try to relieve pain and improve wound healing. 1 Autologous fat grafting (AFG) has been increasingly used in treating scars because of its demonstrated beneficial effect. It is a simple, safe, and repeatable procedure that can be applied in the restoration of skin quality and wound healing.…”
Section: Introductionmentioning
confidence: 99%